2018
DOI: 10.1016/j.learninstruc.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural generalizability of social and dimensional comparison effects on reading, math, and science self-concepts for primary school students using the combined PIRLS and TIMSS data

Abstract: Previous cross-cultural studies of social and dimensional comparison processes forming academic self-concepts (the big-fish-little-pond effect (BFLPE) and Internal-external frame-of-reference (I/E) models) have mostly been based on high-school students and two subject domains. Our study is the first to test the cross-cultural generalizability of both comparison processes across reading, mathematics, and science by combining of the TIMSS and PIRLS 2011 databases (15 OECD countries, 67,386 fourth-graders). Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 40 publications
3
42
1
5
Order By: Relevance
“…According to the BFLPE, students use the average accomplishments of their classmates in one area (e.g., math) as a second basis for the formation of their self‐concepts in the same domain. Applying the logic of the I/E model to the BFLPE results in the prediction that school‐average math achievement has a negative effect on MSC but that the effect of school‐average verbal achievement should be positive (compensatory effects model, Figure G; Marsh ; also Guo, Marsh, Parker, & Dicke, ; Marsh, Parker, & Craven, ; Parker, Marsh, Lüdtke, & Trautwein, ). Strickhouser and Zell () provided support for these predictions using experimentally manipulated feedback to control both frame‐of‐reference effects in relation to other people and other domains.…”
Section: The Importance Of the Self‐concept Constructmentioning
confidence: 99%
“…According to the BFLPE, students use the average accomplishments of their classmates in one area (e.g., math) as a second basis for the formation of their self‐concepts in the same domain. Applying the logic of the I/E model to the BFLPE results in the prediction that school‐average math achievement has a negative effect on MSC but that the effect of school‐average verbal achievement should be positive (compensatory effects model, Figure G; Marsh ; also Guo, Marsh, Parker, & Dicke, ; Marsh, Parker, & Craven, ; Parker, Marsh, Lüdtke, & Trautwein, ). Strickhouser and Zell () provided support for these predictions using experimentally manipulated feedback to control both frame‐of‐reference effects in relation to other people and other domains.…”
Section: The Importance Of the Self‐concept Constructmentioning
confidence: 99%
“…First, the BFLP effect model has mostly been applied in the analysis of the effects of classes or schools on adolescents' or young adults' academic self-concept (e.g., Jonkmann et al 2012;Marsh and O'Mara 2010;Parker et al 2013;Trautwein et al 2006). There is surprisingly scant research testing the BFLP effect among younger primary school students, even though examination of the BFLP effect is particularly interesting with respect to these years when students' selfperception of their academic performance is being formed (see Guo et al 2018;Marsh et al 2015;Pinxten et al 2015;Thijs et al 2010;Trautwein et al 2008;Wouters et al 2013). Fig.…”
Section: The Big-fish-little-pond Effect Modelmentioning
confidence: 99%
“…When focusing on the results from Western countries, the variation in the negative BFLP effect was notably wide among fourth graders: it ranged from − 0.134 in Norway to − 0.482 in Italy. A study by Guo et al (2018), which also focused on the BFLP effect among fourth graders, indicated that the BFLP effect might be weaker in reading than in math.…”
Section: The Big-fish-little-pond Effect Modelmentioning
confidence: 99%
See 2 more Smart Citations